A topical approach to lifespan development - Santrock, John W. (New York : McGraw-Hill, 2012)
Highlights connections among the different aspects of life-span development, including Developmental Connections, Topical Connections, Connecting Development to Life, Connecting with Careers, and Connections through Research
1. The life-span perspective -- 2. Biological processes, physical development, and health -- 3. Cognitive processes and development -- 4. Socioemotional processes and development -- 5. Social contexts of development
Includes bibliographical references and index
Keywords: Developmental psychology